Association of Frailty With the Risk of Mortality and Resource Utilization in Elderly Patients in Intensive Care Units: A Meta-Analysis - Xia, Feiping; Zhang, Jing; Meng, Shanshan; Qiu, Haibo; Guo, Fengmei (Frontiers in Medicine, 2021)
Background: The associations of frailty with the risk of mortality and resource utilization in elderly intensive care unit (ICU) patients remain unclear. To address these issues, we performed a meta-analysis to determine whether frailty is associated with adverse outcomes and increased resource utilization in elderly patients admitted to the ICU. Methods: We searched PubMed, EMBASE, and the Cochrane Library through September 2020 to identify relevant studies that investigated frailty in elderly (≥65 years old) patients admitted to an ICU and compared outcomes and resource utilization between frail and nonfrail patients. The primary outcome was mortality. We also investigated the prevalence of frailty and the impact of frailty on health resource utilization, such as hospital length of stay (LOS) and ICU resource utilization. Results: Eleven observational studies enrolling 62,530 participants (28505 frail and 34126 nonfrail) were finally included. Frailty was associated with an increased risk of in-hospital mortality (nine studies, RR: 1.73; 95% CI: 1.12 to 1.98), short-term mortality (five studies, RR: 1.71; 95% CI: 1.42 to 2.06), and long-term mortality (nine studies, RR: 2.09; 95% CI: 1.58 to 2.75). Subgroup analysis showed that retrospective studies identified a stronger correlation between frailty and hospital LOS (two studies, MD 1.14 d; 95% CI: 0.92 to 1.36, p < 0.00001). Conclusions: Frailty is common in elderly ICU patients, and it is associated with increased mortality and prolonged hospital LOS.